Transformative Pedagogy in Dynamic Digital Learning Environments - Andrew Peter Wilson; Emma Charlotte (CV JK Riset Publishing Group, 2026)
This study examines the enactment of transformative pedagogy within dynamic digital learning environments at Indonesian universities facing rapid technological disruption. The research addresses a critical gap in understanding how educators conceptualize and implement pedagogical transformation when digital tools continuously redefine the possibilities and constraints of teaching and learning. Employing a qualitative multi-site case study design, data were gathered from 32 participants across five higher education institutions through semi-structured interviews, digital artifact analysis, and synchronous and asynchronous learning session observations over twelve months. Findings identify three interconnected dimensions of transformative digital pedagogy: the cultivation of critical digital literacy, the redesign of assessment ecologies for digitally mediated learning, and the emergence of hybrid teacher identities. The study concludes that transformative pedagogy in digital environments requires sustained institutional scaffolding, collaborative professional communities, and a critical stance toward technological determinism. Recommendations address curriculum reform, educator development, and policy frameworks for the digital transformation of Indonesian higher education.